Organizational Commitment, Competence on Job Satisfaction and Lecturer Performance: Social Learning Theory Approach - Amin, Muh. Sirojuddin (Golden Ratio of Human Resource Management, 2022)
The purpose of this study is to measure employee performance seen from the achievement of lecurer work. Furthermore, the research design is structured in such a way that the researcher obtains answers to the research questions. The research sample is 244 lecturer in Indonesia, data collection with online survey. The results showed that organizational commitment had a significant positive effect on job satisfaction. Feel happy, think, emotionally attached, worry, sense of belonging, little choice, alternative, sacrifice, loyal, obligation, loyal, work, one organization, wise, and make a very strong contribution. Competence directly has a significant positive effect on employee job satisfaction. This means that through the competencies possessed by lecturer Competence directly has a significant positive effect on employee performance. Competencies possessed by lecturer give a real meaning to employee performance. Job satisfaction directly has a significant positive effect on employee performance. Organizational commitment indirectly has a positive and insignificant effect on performance through job satisfaction. Competence indirectly has a significant positive effect on performance through job satisfaction.